2013
DOI: 10.4161/hv.22828
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-induced endothelial cell surface heterogeneity directly affects endothelial cell escape from a cell-mediated immune response in vitro

Abstract: Immune-mediated damage to tumor vessels is a potential means of preventing solid tumor progression. Antiangiogenic cancer vaccines capable of inducing this kind of damage include formulations comprised of endothelial cell-specific antigens. Identification of antigens capable of eliciting efficient vaccination is difficult because the endothelial cell phenotype is affected by surrounding tissues, including angiogenic stimuli received from surrounding tumor cells. Therefore, phenotype endothelial cell variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(37 citation statements)
references
References 61 publications
1
36
0
Order By: Relevance
“…Cancer cells change the HMEC surface antigens through a cancer cell type-independent www.taylorandfrancis.commechanism, suggesting that HMEC heterogeneity is a result of differences in the strength of growth signals. 37 This observation led researchers to hypothesize that the tumor would affect the HMEC surface profile in the same manner in vivo as in vitro, and that tumor-induced changes in the HMEC antigenic profile would be a consequence of the magnitude of the growth stimulus. Distance also influences the tumor's effects on the EC antigenic profile.…”
Section: Designing Universal Cancer Vaccines With Defined Safety and mentioning
confidence: 99%
See 3 more Smart Citations
“…Cancer cells change the HMEC surface antigens through a cancer cell type-independent www.taylorandfrancis.commechanism, suggesting that HMEC heterogeneity is a result of differences in the strength of growth signals. 37 This observation led researchers to hypothesize that the tumor would affect the HMEC surface profile in the same manner in vivo as in vitro, and that tumor-induced changes in the HMEC antigenic profile would be a consequence of the magnitude of the growth stimulus. Distance also influences the tumor's effects on the EC antigenic profile.…”
Section: Designing Universal Cancer Vaccines With Defined Safety and mentioning
confidence: 99%
“…37 Previous studies have suggested that k reflects the intensity of tumor-induced changes at the cell surface, and b reflects the immunogenicity of cell surface targets associated with these changes. Variations in k and b have been demonstrated to be interrelated.…”
Section: Designing Universal Cancer Vaccines With Defined Safety and mentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 In many tumour models, CD40-ligand (CD40L)-mediated signals stimulate host anti-tumour immunity [3][4] and significantly increase tumour incidence in Cd40 gene knockout mice. 5 Using CD40 as the target molecule, new biological therapies for cancer have been developed wherein CD40/CD40L signals are stimulated using CD40 antibody, CD40L recombinant products or tumour vaccines with cDNA in order to inhibit tumour growth in epithelial cells.…”
Section: Introductionmentioning
confidence: 99%